Determinan Tingkat Pemahaman Akuntansi Dari Perspektif Gender - Andi Gusnawati; Titik Agus Setiyaningsih (Jurnal Akuntansi dan Governance, 2020)
This study aims to examine the effect of intellectual intelligence, emotional intelligence, spiritual intelligence, learning behavior, and accounting practicum on the level of understanding of accounting as well as looking at the differences based on a gender perspective. This research uses primary data. This study includes research with a quantitative approach. Determination of the sample in this study using Stratafied random sampling technique and technical analysis of the data used is multiple linear regression analysis. The population in this study were S1 Accounting students in 2014 at Muhammadiyah University Jakarta, UIN Jakarta, and STIE Ahmad Dahlan Jakarta, with a total sample of 214 respondents. The results showed that partially intellectual quotient, spiritual quotient, learning behavior, and accounting practicum had a positive and significant effect on the level of accounting understanding while emotional quotienthad no positive and significant effect on the level of accounting understanding. And found differences in intellectual intelligence, emotional intelligence, spiritual quotient between male and female students. While learning behavior, accounting practicum, the level of understanding of accounting there is no difference between male students and female students.